Avaliação do papel da piridoxina na prevenção da nefrocalcinose induzida pela hiperoxalúria em ratos - Cunha, Natália Baraldi [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Introduction: The calcium oxalate is the major metabolic component involved in the formation of renal calculus. Therefore, different pharmacological approaches have been or are being proposed for the treatment of nephrolithiasis by calcium oxalate. Among them, the pyridoxine, a component of vitamin B6, has been suggested as a potential therapeutic agent that can minimize the effects of hyperoxaluria. However, the results are controversial. Objective: To evaluate the effects of pyridoxine (vitamin B6) on the urinary excretion of oxalate and its possible impact on renal disorders caused by nephrocalcinosis induced from an experimental model of hyperoxaluria in rats. Methods: It was used 60 Sprague Dawley male rats and were randomized into four groups: Group 1 [(G1: n = 15) clinical control]; Group 2 [G2: Ethylene glycol (EG) 0.5% + Vitamin D3 (VD3), n = 15], which hyperoxaluria was induced by the administration of EG diluted in water and offered in association with VD3 (Cholecalciferol) at a dose of 0.5 uM; Group 3 [G3: 0.5% EG + VD3 + pyridoxine (VB6); n = 15], which the animals received the same drugs offered to the G2 plus VB6 at a dose of 180mg / kg body weight / day; Group 4 (G4, n = 15) which the animals are supplemented only with the same dose of VB6 in G3. All animals were euthanized after 28 days of intervention and submitted a metabolic study on the urine of 24 hours; histopathological / morphometric analysis of oxidative stress in renal parenchymal and spectroscopic measurement of calcium. Results: Among the urinary parameters evaluated, there was significant reduction in the citrate in G2 compared to the control group- G1 (781.9 and 2414.4mg / L, respectively), while the oxalate was significantly increased in G2 and G3 compared to G1 (7.79, 8.94 and 2.96mg / L, respectively). The urinary calcium was significantly lower in the induced groups (G3: 0.9, G2: 1.5 and G1: 2.25mg / dL). Histomorphometric analysis revealed that only the animals of G2 and G3 developed nephrocalcinosis without, however, no substantially differences from each other in the counting of intratubular crystals were found. Similarly, considering the histopathologic analysis, only the induced animals (G2 and G3) exhibited atrophy, stromal extravasation and inflammatory infiltrate in the renal parenchyma in a similar pattern between the two groups. Regarding to the analysis of oxidative stress, an increase of lipid hydroperoxide levels associated with reduced superoxide dismutase activity and glutathione peroxidase in the G2. In the other groups, the enzyme pattern remained relatively stable compared to the control, except for catalase activity, which activity proved to be increased in all groups. In the other groups, the enzyme pattern remained relatively stable compared to the control (G1), except for the catalase activity, in which activity increased in all groups. As expected, the quantification of calcium in the renal parenchyma was significantly higher in G2 and G3 as compared to groups without induction. Conclusion: Pyridoxine was not able to produce a significant effect in the treatment and / or prevention of urinary disorders, as well as morphological, inflammatory and functional renal tissue in rats with secondary hyperoxaluria obtained from the administration of inducing agents.

Introdução: O oxalato de cálcio (OxCa) é o principal componente metabólico envolvido na formação dos cálculos renais. Por esta razão, diferentes abordagens farmacológicas foram ou estão sendo propostas para o tratamento da nefrolitíase por OxCa. Dentre elas, a piridoxina, um componente da vitamina B6, tem sido sugerida como potencial agente terapêutico capaz de atenuar os efeitos da hiperoxalúria, porém com resultados ainda controversos. Objetivo: Avaliar os efeitos da piridoxina (Vitamina B6) sobre a excreção urinária de oxalato e seu eventual impacto nas alterações renais causadas pela nefrocalcinose induzida a partir de um modelo experimental de hiperoxaluria em ratos. Métodos: Foram utilizados 60 ratos machos da raça Sprague-Dawley, randomicamente distribuídos em quatro grupos: GRUPO 1 (G1: n=15) controle clínico; GRUPO 2 [G2: Etilenoglicol (EG) a 0,5%+vitamina D3 (VD3), n=15] no qual a hiperoxalúria foi induzida a partir da administração de EG diluído em água e ofertado em associação com a VD3 (Colecalciferol) na dose de 0,5 μM; GRUPO 3 [G3: EG 0,5%+VD3+Piridoxina(VB6); n=15] onde os animais receberam as mesmas drogas ofertadas ao G2 acrescido da VB6 na dose de 180mg/kg peso/dia; GRUPO 4 (G4, n=15) animais suplementados apenas com a VB6 na mesma dose do G3. Todos os animais foram eutanasiados após 28 dias de intervenção e submetidos a estudo metabólico na urina de 24 horas; análise histopatológica/morfométrica, análise do estresse oxidativo no parênquima renal, bem como dosagem espectroscópica do cálcio. Resultados: Dentre os parâmetros urinários avaliados, observou-se significativa redução do citrato no G2 em relação ao controle (781,9, e 2414,4mg/L, respectivamente), enquanto que o oxalato mostrou-se significativamente aumentado nos G2 e G3 quando comparado ao G1 (7,79; 8,94 e 2,96mg/L, respectivamente). O cálcio urinário foi significativamente menor nos grupos induzidos (G3:0,9, G2:1,5 e G1: 2,25mg/dL). A análise histomorfométrica revelou que apenas os animais dos G2 e G3 desenvolveram nefrocalcinose sem, no entanto, apresentar diferença significativa entre si na contagem dos cristais intratubulares. Da mesma forma, considerando-se a análise histopatológica, apenas os animais induzidos (G2 e G3) exibiram atrofia, extravasamento estromal e infiltrado inflamatório no parênquima renal, em um padrão bastante semelhante entre os dois grupos. Com relação à análise do estresse oxidativo, houve aumento dos níveis do hidroperoxido de lipídeo associado à redução da atividade da superoxido dismutase e glutationa peroxidase no G2. Nos demais grupos, o padrão enzimático manteve-se relativamente estável em relação ao controle, com exceção da atividade da catalase, cuja atividade revelou-se aumentada em todos os grupos estudados. Como esperado, a quantificação do cálcio no parênquima renal foi significativamente maior em G2 e G3 quando comparado aos grupos sem indução. Conclusão: A piridoxina não foi capaz de produzir um efeito significativo no tratamento e/ou na prevenção das alterações urinárias, bem como morfológicas, inflamatórias e funcionais do parênquima renal de ratos com hiperoxalúria secundária obtida a partir da administração de agentes indutores.
Evaluation of pyridoxine on prevention of nephrocalcinosis in rats induced by hyperoxaluria
Keywords: Piridoxina; Nefrocalcinose; Ratos; Etileno glicol; Pyridoxine; Nephrocalcinosis; Rats; Ethylene glycol